KERUSAKAN TEGANGAN TINGGAL AKIBAT PENYARADAN DENGAN TRAKTOR PADA BERBAGAI TINGKAT KERAPATAN TEGAKAN - Dulsalam Dulsalam; Sukanda Sukanda; Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 1989)
An  investigation   on  residual   stand  damages  caused  by skidding  tractor  on several stand  density   levels was carried out  at PT Sumpol   Timber  in South  Kalimantan  in 1987.  Forty   five  sample plots  were selected  randomly  in this research. The purpose   is to gather  information   about  the resdiual stand damages caused by skidding  tractor on several stand density levels.   The  result  of  investigation   reveals that  :                                                                                                                                                                                              1.  The number    of  trees  having   diameter   of  20  cm  and  up  varies   from  80   to  300  trees/ha  with  an  average of  190.22 trees/ha.                                                                                                                                               2.  The  residual stand  damages  for  the  area with  stand  densities  ot < 150,  150 -199,   and >  200  trees/ha  were 16,  7, 28.3,and  39. 0 trees/ha,  respectively.   They  are significantly   different.3.  It  is suggested  that   the  skidding   operations,    especially   in  high  stand  density   levels, be done  with  better  planning   in-order  to save powers,  costs  and  resources.